PENGARUH PENGGUNAAN MEDIA PLAYDOUGH TERHADAP KEMAMPUAN MOTORIK HALUS DAN KREATIVITAS ANAK KELOMPOK B DI TK KHADIJAH 8 KABUPATEN BANYUWANGI - Nuraini, Erina; Waris, Waris; Kustiyowati, Kustiyowati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
Abstract In daily practice at Kindergarten (TK) schools there are problems and the development of children's fine motor skills, children's fine motor skills appear not to be optimal, this is due to the lack of stimulation given to children, lack of balance in the child's body in every movement. The method in the fine motor learning process that is used is not optimal. The purpose of this study was to determine the effect of using playdough media on fine motor skills and creativity in group B TK Khadijah 8 Banyuwangi Kindergarten. Fine motor development is related to the development of the ability to use fingers to use various activities such as sticking, pinching, cutting, painting and others. The research method used is the Pre Experimental Design method with the One Group Pretest-Posttest Design research design. The data used to obtain the data are as follows: observation, interviews, documentation. The statistics used are independent t-test and sample t-test. Research results. Playdough improves children's fine motor skills and creativity. Playdough media play activities can hone children's fine motor skills because they use their hands and fingers as well as eye coordination. Then the selected tool is easier to obtain. In conclusion, the use of playdough media has an effect on fine motor skills and creativity of group B children in Khadijah 8 Kindergarten, Banyuwangi Regency. Keywords. Media Playdough, fine motor, creativity, Kindergarten